2019
DOI: 10.12688/f1000research.17058.1
|View full text |Cite
|
Sign up to set email alerts
|

A high dose of total recombinant FSH suppresses granulosa cell apoptosis and maintains oocyte quality in endometriosis: A cross-sectional study

Abstract: Background: Endometriosis is one of the most common conditions causing infertility and an indication to undergo in vitro fertilization (IVF). High apoptosis rate and oxidative stress in patients with endometriosis are believed to negatively affect the IVF success rate. However, there have been conflicting results on the effect of endometriosis on IVF success, and there have been limited studies that directly assess endometriosis and its effect on oocyte qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Importantly, the incidence of apoptosis in granulosa cells has been linked to the quality of the oocytes and to the pregnancy outcome ( 34 36 ). There is some evidence indicating that the administration of HP-hMG increases the apoptosis of cumulus cells compared to r-hFSH or urinary FSH ( 37 ), and a recent study showed that high doses of r-hFSH suppress the apoptosis of granulosa cells in patients with endometriosis undergoing IVF ( 38 ). Therefore, researchers are currently exploring the consequences of the different protocols of gonadotropin ovarian stimulation on the apoptosis rate of granulosa cells ( 35 , 39 ).…”
Section: The Differential Effects Of Gonadotropin Treatments On Oocyte – Granulosa Cell Communication and Follicular Maturationmentioning
confidence: 99%
“…Importantly, the incidence of apoptosis in granulosa cells has been linked to the quality of the oocytes and to the pregnancy outcome ( 34 36 ). There is some evidence indicating that the administration of HP-hMG increases the apoptosis of cumulus cells compared to r-hFSH or urinary FSH ( 37 ), and a recent study showed that high doses of r-hFSH suppress the apoptosis of granulosa cells in patients with endometriosis undergoing IVF ( 38 ). Therefore, researchers are currently exploring the consequences of the different protocols of gonadotropin ovarian stimulation on the apoptosis rate of granulosa cells ( 35 , 39 ).…”
Section: The Differential Effects Of Gonadotropin Treatments On Oocyte – Granulosa Cell Communication and Follicular Maturationmentioning
confidence: 99%